Revitalization of the Nepalese Agriculture Sector for Economic Prosperity: Gap Analysis between Agricultural GDP and Investment Trends (The Journal of Economic Concerns, 2024)
This study explores the paradox of the decreasing contribution of agriculture to GDP despite rising investments in the sector, conducting a gap analysis between agricultural GDP and investment trends. The anticipated outcome of increased agricultural investment is enhanced productivity and a corresponding rise in GDP share. However, this study identifies a significant mismatch between investment trends and agricultural output, revealing discrepancies that require attention. By analyzing relevant data, the research highlights the troubling trend of diminishing agricultural GDP contribution alongside increasing imports, emphasizing the urgent need for sectoral revitalization to foster economic prosperity. The paper argues that the current economic environment presents substantial challenges to agricultural revitalization and stresses the necessity of improved coordination and cooperation among stakeholders.